Frequency of Preoperative Anxiety in Patients Undergoing Maxillofacial Surgery at Tertiary Care Centre - Rizwana; Jehan Alam; Ruqayya Shah; Abubakar Saddique; Fatima (Medical Journal of South Punjab, 2025)
Objective: To determine the frequency of preoperative anxiety among patients planned for elective maxillofacial surgery Methodology: A descriptive cross-sectional study?was done at Jinnah Postgraduate Medical Centre, Karachi, (a tertiary hospital) in the Department of Oral and Maxillofacial surgery, for duration of six months from 12th July 2024 to 11th January 2025. Preoperative anxiety was assessed using the Corah’s Dental Anxiety Scale score, a validated tool with two dimensions measuring anxiety levels and the need for?information. One of the most used instruments for evaluating dental anxiety is the Corah’s Dental Anxiety Scale (DAS). Results: A total number of 167 patients were included in our study. The mean age of the patients was 36.98±6.94 years. There were 32 (19.2%) patients who had aged ?30 years and 135 (80.8%) patients who were aged >30 years. In this study, 128 (76.6%) patients had anxiety, and 39 (23.4%) patients did not. The mean Corah’s Dental Anxiety Scale score of anxiety and non-anxiety patients was 13.42±3.32 and 5.64±1.48, respectively. Conclusion: Our study underscores the high prevalence of preoperative anxiety 76.6% among maxillofacial surgery patients and its association with various demographic and socioeconomic factors. Anxiety was relatively high in young patients and in females